Trisystems Engineering Sdn Bhd / Siti Maryam Azman - Azman, Siti Maryam (Universiti Teknologi MARA, Perlis, 2024)
According to the lesson plan, students under Bachelor of Business Administration (Hons.) Human Resource Management must finish their degree with industrial training as their final semester subject. In addition, this report will detail my remarkable and enlightening 6- month industrial practical training experience, which began at a company named Trisystems Engineering Sdn Bhd. First and foremost, I am grateful to Allah, my internship advisor, Trisystems personnel, particularly those in the human resources department, as well as my family and friends, for providing me with the motivation and strength to complete my 24-week internship and write my report. Aside from that, I did send the updated resume version to my profile. My phone number, email address, objectives, technical and personal abilities, schooling, employment experiences (including my most recent experience as a trainee), extra-curricular activities, and previous academic accomplishment were all included into it. Following that, it is critical for me to comprehend and have a clear perspective of what the organization is doing. Trisystems Engineering Sdn Bhd is a corporation that provides oil and gas sector products and services. As an organization, a logo is essential because it was one of the marketing techniques used to present Trisystems to clients and consumers. This is due to the fact that it may describe the features that Trisystems wishes to emphasize. For the entire six-month period, I was assigned to work under the Human Resource and Administration Department, and I gained a variety of new knowledge, friends, experiences, and skills such as contacting food suppliers, editing slides, assisting in the organization of CSR (Community Service Responsibility), and emailing to other organizations. A SWOT (strengths, weaknesses, opportunities, and threats) analysis is also essential. I must also research the political, economic, social, technological, environmental, and legal issues of the external environment. A PESTEL analysis is used to identify threats and weaknesses in preparation for a SWOT analysis. As a result, each item will be thoroughly explained throughout this report.